Analysis and systematization of elementary tasks with materials handling - Rodić, Milorad; Novaković, Dragoljub; Stević, Miodrag (Journal of Production Engineering, 1994)
The paper analyzes and systematizes elementary tasks in materials handling. Primary consideration is given to factors which influence the conception of the device which is given the task of realization of certain materials handling functions. At the same time, requirements of modern machining and assembly systems for a more substantial cut down in auxiliary times are given due consideration. The following part of the paper defines basic functions of materials handling as well as most frequently used devices. The paper concludes with a global concept of determination of materials handling functions and design of devices for their implementation.